De la palabra al género : un itinerario - Daniel Link (Cuadernos LIRICO)
After evoking the figure of Ana María Barrenechea the article focuses on a new interpretation of Borges writings considered as an universal language of argentine literature and literary criticism, a language that bears a theory of reading and, in the same time, challenges any reading. The main issue addressed here is the relationship of Borges work with the mechanics of repetition and subsequently with the mass media. The article takes into account hypothesis of Deleuze, Nietszche, Kirkegaard, Lacan about the philosophical problem of repetition and the artistic creation process. The author analyses the way Borges highlights the copy and the rewriting ; his texts reveal these patterns of the production in series as key of their own logic.